University proceedings. Volga region. Natural sciences - M.I. Egorov; D.G. Smirnov; N.V. Shulaev; V.R. Saitov; А.A. Zaripov; A.S. Gridneva; A.R. Fattakhova (Известия высших учебных заведений. Поволжский регион: Естественные науки)
Background. Reliable information on the species composition and ecological characteristics of bats, especially in protected areas, is necessary for adequate planning and implementation of monitoring and conservation measures for both their populations and the natural communities they inhabit. However, due to poorly studied bats in the Republic of Tatarstan this is not possible. In order to solve this problem, we started their targeted studies. The purpose of the study was to summarize the data we obtained on the capture of bats in recent years in several protected areas. Materials and methods. Studies were conducted from May to August 2022–2024 at two sites of the Volga-Kama Nature Reserve, Kichki-Tan Sanctuary and Selengushka Lake, Nurlat District. Bats were captured with spider nets. Results. Sixty-two individuals of 7 species of bats were captured during the work conducted at four locations: Myotis nattereri, M. brandtii, M. daubentonii, M. dasycneme, Nyctalus. noctula, Pipistrellus nathusii and P. pygmaeus. The finding of M. brandtii and P. pygmaeus were made in protected areas for the first time. Conclusions. M. daubentonii, M. dasycneme, N. noctula, P. nathusii and M. brandtii were found to be the most common species. M. nattereri, P. pygmaeus and N. lasiopterus should be considered as minor species. As a result, the total species composition of bats in the considered sites is currently represented by 10 species, which is 76,9 % of the entire bat fauna of Tatarstan.